1232. Phylogenomics of Enterococcus faecium From South America: Revisiting Worldwide VRE Population Structure. (26th November 2018) - Rios, Rafael; Reyes, Jinnethe; Carvajal, Lina P; Kolokotronis, Sergios-Orestis; Planet, Paul; Narechania, Apurva; Munita, Jose; Arias, Cesar; Diaz, Lorena
Abstract: Background: Previous studies have suggested that the population structure of E. faecium is composed of two main clades; a commensal clade (designated clade B) and a hospital-associated clade (Clade A) that encompass most of the clinical and animal isolates. The phylogenetic analyses leading to these results have been accomplished with the notable absence of isolates from diverse geographical regions (including South America). We aimed to refine the worldwide population structure of E. faecium by including 55 representative genomes from isolates obtained from five Latin American countries recovered between 1998 and 2014. Methods: We sequenced our 55 representative isolates and selected other 285 genomes, from public databases, obtained across different regions (36 countries), different sources (animal, commensal, and clinical strains) and a wide range of dates of isolation (1946–2017). We characterized the genomes by presence/absence of resistance, virulence and mobile elements, and of CRISPR- cas systems. We analyzed the phylogeny of the entire population, selected the genomes belonging to clade A to examine recombination patterns and performed Bayesian molecular clock analysis excluding recombinant regions. Results: Two major clades were identified, as previously reported. However, a higher degree of variation in clade A was found. Indeed, we identified a subclade (subclade I) that diverged ~894 years ago, and clearly distinguished clinical isolates from those of animal origin (distributed among a number of smaller early-branching subclades). A further split within the clinical subclade (subclade II) that diverged around ~371 years ago was also evident. Latin American isolates were distributed within subclades I (48%) and II (42%). Isolates in "animal" branches exhibited an average recombination of 34 Kbp, where it was 5 Kbp and 21 Kbp for subclades I and II, respectively. More resistance determinants were found in subclade II (62%), followed by I (54%) and absence of cas was the norm in the clinical subclades. Conclusion: Inclusion of E. faecium isolates from diverse geographical region supports a continuous evolution of these organisms causing human infections. Important evolutionary events seem to favor emergence of novel subclades capable to cause important morbidity and mortality. Disclosures: J. Munita, Pfizer: Grant Investigator, Research grant. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support. MeMed: Grant Investigator, Research support. Allergan: Grant Investigator, Research support.